Estimating in heavy construction : roads, bridges, tunnels, foundations - Jacob, Dieter; Müller, Clemens (Editor); Einstein, Herbert H. (Ernst & Sohn, 2017)
This book is a valuable source of knowledge for everyone involved in estimating for heavy construction projects. It explains the strategies of heavy contractors and their implications for cost estimating. The core part of the book presents the theoretical background of estimating as well as best practice examples from large-scale international construction projects. In contrast to other publications on estimating, this book presents specific numbers, and the costs are calculated precisely.
Keywords: Building -- Estimates.; Civil engineering.; elektronické knihy; electronic books